The Effect Of Nutrition Literacy Education on Food Labels through Audio Visual Media on the Behavior of Student at SMA Negeri 4 Kendari in Choosing Packaged Foods - Dewi, Radya Permala; Lisnawaty, Lisnawaty; Salsabila, Syefira (Universitas Airlangga, 2025)
Background: Packaged food is a very popular food among teenagers because it is part of teenage socialization. Teenage consumers generally choose food according to taste without paying attention to nutritional content. The ability to understand labels on food products is expected to increase teenagers awareness of being more selective in choosing packaged foods. Increased understanding is achieved through nutrition education in an effort to improve food label reading behavior. Audio-visual learning media was chosen because it is able to activate the senses of sight and hearing, thus helping to increase focus in learning. Objectives: The purpose of this study was to determine the effect of food label literacy nutrition education through audiovisuals on the behavior of high school students of SMA Negeri 4 Kendari in choosing packaged food. Method: This research used a pre-experimental method with one group pretest-posttest, which involved 93 students of classes X and XI in SMA Negeri 4 Kendari. Samples were selected using proportional random sampling. Data analysis in this study was carried out with the McNemar test at the α=0.05 significance level. The event took place at SMA Negeri 4 Kendari using audiovisual media. A validated questionnaire instrument was used to measure food labeling behavior before and after the intervention. Results: Based on the research, it was found that all respondents had sufficient knowledge (100%), good attitudes (100%), and good actions (100%). Thus, there is an effect of food label literacy nutrition education through audiovisual on knowledge (ρ=0.000), attitudes (ρ=0.000), and actions (ρ=0.000) in choosing packaged food at SMA Negeri 4 Kendari students. Conclusion: Thus, food label literacy nutrition education through audio visuals can significantly affect knowledge, attitudes, and actions about food labels in choosing packaged foods.